Development of thiamine-rich snacks from brown rice using extrusion technology. Issue 5 (22nd December 2020) - Bhat, Tashooq; Hussain, Syed Zameer; Naseer, Bazila; Hameed Rather, Abdul; Ahmad Mir, Shakeel
Abstract : Purpose: Snack industry is one of the fastest growing food sectors globally, and people are nowadays conscious about intake of healthy snacks on regular basis. There is enormous variety of ready-to-snacks available in the market. Brown rice though highly nutritious in comparison to polished rice is consumed meagerly by masses. Each raw material/ingredient used in extrusion cooking requires specific control of processing variables to meet acceptable product characteristics and consumer demands, which in turn necessitates the need to optimize the conditions for development of brown-rice-based snacks. The aim of this study was to optimize the extrusion cooking conditions for development of brown-rice-based extrudates. Design/methodology/approach: Extrusion conditions were optimized through design expert using central composite rotatable design (CCRD) experimental design. The effect of feed moisture (10–22%), screw speed (215–385 rpm) and barrel temperature (95–160 °C) on specific mechanical energy (SME), bulk density (BD), water absorption index (WAI), water solubility index (WSI), expansion ratio (ER), breaking strength (BS) and instrumental color (L*, a*, b*) was evaluated. Findings: All the system and product responses were significantly ( p  < 0.01) affected by independent variables. Regression models obtained were highly significant with high coefficient of determination ( R 2  = 0.992). The optimum extrusion conditions obtained by numerical optimization for development of snacks were moisture content of 12%, screw speed of 350 rpm and temperature of 133 °C. The vitamin B1 content of brown-rice-based snacks was 0.45 mg/100 (50% of RDA) whereas no vitamin B1 was detected in white-rice-based snacks used as control. Practical implications: The developed snacks contain 0.45 mg/100 g of vitamin B1 . If a person on an average consumes 150 g of snacks in a day, 50% of RDA (1.2 mg/day) for vitamin B1 can be sufficed. Therefore, developed snacks can prove to be a viable vehicle to reduce the vitamin B1 deficiency burden among the target population. Large-scale production and consumption of such type of snacks could improve the nutritional status of vitamin B1 deficient people. Furthermore, it can also provide a good opportunity for snack industry to develop nutritious snacks through utilization of brown rice. Originality/value: Brown rice flour contains nutrients such as iron, calcium, zinc, sodium and vitamin B1 in appreciable portions and was thus explored for development of nutritious snacks. Moreover, developed snacks recorded an overall acceptability of 4.70 out of 5, which depicts it is acceptable for mass production and consumption.